Knowledge of Paramedical Staff Regarding Drugs Addiction in Baghdad City/ Iraq - najem, shymaa; Mousa, atta (Iraqi National Journal of Nursing Specialties, 2018)
Objectives: To determine the level of knowledge regarding drugs addiction among paramedical staff; and toidentify the association between the level of knowledge and their socio-demographic variable.Methodology: A cross-sectional study was Conducted in Baghdad on Staff for the period from 1st June,2016 to30th September, 2016 . The sample included 510 Health professionals . There are 9 sectors in centerof Baghdad , 5 of them in Al- Kurkh side of the city and 4 in Al-Russafa side. The sample was selected from49 primary health care centers and 8 public hospitals through a multi-stage sample using a simple randomsampling technique. The information was collected through the design of a questionnaire whose stability andreliability were determined. Data analysis was done using descriptive and indicative descriptive statisticalmethods.Results: The results of the examination demonstrated that 21.8% of the health staff in the age group (40-44)were the majority of the study sample for males (51.2%) and about (85.9%) of the married while the majority(87.1% Of the city's population. The educational level was the majority of graduates of medical institutes(62.4%). No significant association was found between level of education and knowledge about drugaddiction for paramedical staff .No significant association had been found between gender, marital status,and residence with knowledge about drug addiction for paramedical staff.Recommendations: Paramedical staff might be needed to adhere to educational programs and nationaltraining as intensive courses for short period, about of drug addiction. And national education programs aboutdrug addiction to prevent constructed and presented to the public through the collaboration between the healthauthority and society association and non-governmental organizations